1995
DOI: 10.2214/ajr.165.3.7645465
|View full text |Cite
|
Sign up to set email alerts
|

Helical CT of the upper airway: normal and abnormal findings on three-dimensional reconstructed images.

Abstract: Imaging

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…The CT scans were done helically (High-Speed Advantage; General Electric Medical Systems, Milwaukee, Wis) during slow inspiration or expiration using a 3-or a 5-mm-section thickness and a helical pitch of 1.0 or 1.3. [23][24][25] The CT scans were processed using a surface-rendering technique (virtual endoscopy) that sculpts away all soft tissues of the neck and produces a 3-dimensional model of the airway contour. 26 Data were displayed on a specialized computer workstation (Indigo 2 Maximum Impact; Silicon Graphics, Mountain View, Calif) capable of interactive manipulation and "fly-through visualization" (ie, simulated endoscopy) of the 3-dimensional models.…”
Section: Imaging Studiesmentioning
confidence: 99%
“…The CT scans were done helically (High-Speed Advantage; General Electric Medical Systems, Milwaukee, Wis) during slow inspiration or expiration using a 3-or a 5-mm-section thickness and a helical pitch of 1.0 or 1.3. [23][24][25] The CT scans were processed using a surface-rendering technique (virtual endoscopy) that sculpts away all soft tissues of the neck and produces a 3-dimensional model of the airway contour. 26 Data were displayed on a specialized computer workstation (Indigo 2 Maximum Impact; Silicon Graphics, Mountain View, Calif) capable of interactive manipulation and "fly-through visualization" (ie, simulated endoscopy) of the 3-dimensional models.…”
Section: Imaging Studiesmentioning
confidence: 99%
“…Spiral CT provides cross-sectional images with assessment of the size and localization of a tumor [5,7,8] and enables visualization of peribronchiolar morphologic information not available by bronchoscopy [9,10]. Spiral CT allows obtainment of volumetric data during a single breath-hold scanning and the procedure is well tolerated by patients [5,11,12,13,14,15,16,17,18]. Recent studies have shown the feasibility of 3D surface rendering of the tracheobronchial tree and the advantages of using multiplanar reconstructions [12,19].…”
mentioning
confidence: 99%
“…Besides these positive values, to demonstrate the postoperative anatomy perfectly with these techniques is not always easy. In last years, CT technology advanced tremendously and 3D-CT has gained popularity and wide acceptance in many disciplines including also urology [4][5][6][7]. Spiral CT, allows the source and detectors to radiate continuously in a single direction while X-ray exposure are obtained.…”
Section: Discussionmentioning
confidence: 99%
“…Although, these techniques give knowledge to the clinician about pathologic conditions and functional quality of the pouch, they may not show the postoperative surgical anatomy perfectly. In last years 3-dimensional computerized tomography (3D-CT) gained a wide acceptance and have been used in many disciplines including urology [4][5][6][7]. In urology, 3D-CT has been commonly used for renal imaging in order to understand the preoperative anatomy better, especially, in partial nephrectomy candidates and renal vascular disease [8,9].…”
Section: Introductionmentioning
confidence: 99%